How does thyroidectomy for benign thyroid disease impact upon quality of life? A prospective study. Issue 12 (25th September 2020) - Chew, Carolyn R.; Chin, Synn Lynn; Lam, Tracey; Drosdowsky, Allison; Chan, Steven T. F.; Chin‐Lenn, Laura
Abstract: Background: Choosing which patients to recommend surgery for benign thyroid conditions can be difficult due to the subjective nature of compressive thyroid and hormonal symptoms. The aim of this prospective study was to analyse changes in quality of life (QOL) following thyroid surgery using a validated disease‐specific assessment tool, the thyroid‐related patient‐reported outcome (ThyPRO) questionnaire. Methods: Participants undergoing elective thyroid surgery for benign conditions were recruited. Patient demographics and clinical data were collected. ThyPRO consists of 85 questions grouped into 13 physical, mental and social symptom domains. Patients completed a ThyPRO questionnaire pre‐operatively and at 6 weeks and 6 months post‐operatively. ThyPRO items were scored according to protocol to produce 13 subscales. Repeated measures linear models with no random effects were performed using data for each outcome. Results: Results were available for a total of 72 patients. The sample was predominately female ( n = 63, 88%) with average age 49.8 years. The majority of patients underwent surgery for multi‐nodular goitre. At 6 weeks post‐operatively, significant improvement was demonstrated in the goitre, hypothyroid, hyperthyroid and anxiety symptom domains. At 6 months post‐operatively, significant improvement was demonstrated in all but four domains. No domains demonstrated significant increase in impairment post‐operatively. Conclusion: Patients had significant improvement in nine of 13 symptom domains following surgery. Patients did not experience a negative impact on QOL following surgery. Further studies with larger patient cohorts may be able to identify potential pre‐operative predictive factors for a post‐operative improvement in QOL for benign thyroid disease. Abstract : Use of validated quality of life questionnaire (ThyPRO) to assess quality of life following benign thyroid surgery in an Australian population.